Role of SUV39H2 in shaping the malignant phenotype of triple-negative breast cancer - Wang, Zhi-Wen; Hu, Shuang; Chen, Yong; Lu, Yong; Li, Shang-Fu; Deng, Yang; Jiang, Hai-Tao (Frontiers in Oncology, 2026)
BackgroundSUV39H2, a histone methyltransferase involved in H3K9 trimethylation and transcriptional silencing, has been implicated in cancer progression. However, its expression patterns, clinical relevance, and functional roles in various tumor types remain to be fully elucidated.MethodsSUV39H2 expression in multiple cancers and paired adjacent normal tissues was analyzed using the TCGA-GTEX database and Xiantao online tools. Prognostic significance was assessed by survival analysis. KEGG and GO enrichment analyses were conducted to explore potential functional roles. Immune infiltration correlations were evaluated based on TCGA data. Single-cell RNA sequencing from GSE176078 was analyzed for validation of expression patterns. Immunohistochemistry (IHC) was performed on five pairs of TNBC patient samples to confirm SUV39H2 expression. Western blotting (WB) was conducted to verify SUV39H2 knockdown efficiency in MDA-MB-231 and Hs-578T TNBC cells. Functional assays, including Transwell migration, colony formation, sphere formation, and subcutaneous xenograft tumorigenicity assays, were performed to evaluate the effects of SUV39H2 knockdown on TNBC cell growth and metastatic potential.ResultsSUV39H2 was significantly overexpressed in multiple cancers, with consistently elevated levels in paired tumor-adjacent tissues. In TNBC, SUV39H2 expression was markedly upregulated across all clinical and TNM stages compared with normal tissues and other BRCA subtypes. Immunohistochemistry confirmed SUV39H2 overexpression in TNBC patient samples, and WB demonstrated successful knockdown in MDA-MB-231 and Hs-578T cells. Functional assays revealed that SUV39H2 knockdown significantly inhibited proliferation, migration, stemness, and in vivo tumorigenicity in TNBC cells.ConclusionsSUV39H2 is consistently upregulated in triple-negative breast cancer and is associated with malignant features including enhanced proliferation, migration, stemness, and in vivo tumorigenicity. Functional and clinical evidence highlights SUV39H2 as a potential diagnostic biomarker and therapeutic target in TNBC, although its clinical utility requires further validation.